Assessment of the knowledge and practices regarding standard precaution among nursing staff at a tertiary care hospital of Raipur city, Chhattisgarh - Rochwani, Ritu; Sharma, Mini (International Journal Of Community Medicine And Public Health, 2019)
Background: Nurses as healthcare providers obliged to protect herself and patients against infections. Therefore, nurses should have knowledge and strict adherence to standard precautions. Hence, this study was undertaken to assess the knowledge and practices of nursing staff regarding standard precautions. Aims and objectives of the study were to assess the knowledge of nursing staff regarding standard precaution and to observe the practices of nursing staff regarding standard precaution. Methods: This was a cross sectional study conducted among staff nurses working in Bhim Rao Ambedkar Memorial Hospital, Raipur, and Chhattisgarh, from January to March 2017 among 100 staff nurses. Pretested predesigned semi-structured questionnaires were used. Data collected were entered in Microsoft excel sheet. The statistical analysis was done by using epi info 7. Frequencies and percentage were presented for categorical variables. Results: The overall knowledge regarding standard precaution were excellent (>75% score) in 8% nurses. Good knowledge (50 to 75%) in 83% and average (25 to 50%) in 9%. The Practises regarding standard precautions among the nurses were good in 72%, excellent in 17% and average in 11%. Conclusions: Based on the findings of the present study, it can be concluded that in spite of having good knowledge regarding standard precaution among the nurses, practices were not to up to the mark.